A Comparison Between Two Public Expenditure Management Systems in Africa - Lienert, Ian. (Washington, D.C. : International Monetary Fund, 2003)
This paper assesses the advantages and disadvantages of the French and British public expenditure management systems as used in Africa. The main differences are in budget execution and government accounting. In both francophone and anglophone Africa, there are common weaknesses in the application of the inherited systems, which appear to dominate any distinct features of the individual systems. Desirable reforms in both systems will only be successful if they are accompanied by measures that enhance the accountability of those who operate the systems, including enforcing the rules embodied in existing or reformed regulatory frameworks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet